Implementation of al-Attas’s Islamization on the Impact of Desacralization of Politics - Pramono, Muhamad Fajar; Sahidin, Amir (Journal of Islamic and Occidental Studies, 2023)
Desacralization of politics is a thought born from a Western secular perspective, aiming to separate religion from politics. It has a bad influence on human life both in epistemologically and methodologically aspects. In addition, this thought also had an impact and was adopted by Muslim scholars, one of which was Ali Abdul Raziq in his secular political theory. Ali argues that "The message of the Prophet is purely a religious message", and "Political matters are only a matter of reason and human experimentation". As an effort to diagnose and treat the negative impact of desacralization of politics on these Muslim scholars, it is necessary to implement the Islamization of knowledge initiated by al-Attas. Through library research with a descriptive analysis approach, it can be concluded that, firstly, the Islamization of knowledge can be carried out in two steps, de-westernization and integration. Secondly, as a result of this Islamization, Ali Abdul Raziq's political thought which was originally secular can be Islamized into, "The message of the Messenger of Allah is a treatise that covers the affairs of the world and the hereafter" and "Political matters must be left to revelation, reason and human experimentation which do not conflict with revelation.